Detection of avian reovirus antibodies in layer birds of small scale commercial farms in Dinajpur district of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The present study was conducted on layer birds of different age groups to determine specific antibody titer level against avian reovirus (ARV) by indirect enzyme linked immunosorbent assay (iELISA) at Dinajpur district of Bangladesh. This study showed that ARV specific antibody positive cases were 84 out of 90 blood serum samples and the highest antibody titer was 26120 and lowest antibody titer was 288. The total 93.33% sera samples were showed positive result. The study showed that 100% sera sample were positive against ARV at 6 weeks of aged group and the highest, lowest and mean antibody titer were 13917, 4895 and 10269 respectively. On the other hand 88.88% sera sample were positive against ARV at 10 weeks of aged group and the highest, lowest and mean antibody titer were 9779, 288 and 5689.89 respectively. The sera sample collected from 14 weeks of aged group showed 88.88% positive and the highest, lowest and mean antibody titer were 11727, 871 and 5250 respectively. The sera sample collected from 18 weeks of aged group showed 88.88% positive against ARV and the highest, lowest and mean antibody titer were 24440, 1234 and 12648.89 respectively. The sera sample collected from 22 weeks of aged group were 100% positive against ARV and the highest, lowest and mean antibody titer were 26120, 1752 and 11373.89 respectively. The sera sample collected from 26 weeks of aged group showed 100% positive against ARV and the highest, lowest and mean antibody titer were 8566, 1630 and 4327.44 respectively. The sera sample collected from 30 weeks of aged group showed 100% positive against ARV and the highest, lowest and mean antibody titer were 13431, 1989 and 5890.56 respectively. The sera sample collected from 40 weeks of aged group showed 77.77% positive against ARV and the highest, lowest and mean antibody titer were 14618, 433 and 5103.22 respectively. The sera sample collected from 48 weeks of aged group showed 88.88% positive against ARV and the highest, lowest and mean antibody titer were 14553, 957 and 7436.5 respectively. In conclusion it is evident that avian reovirus-specific antibody was successfully detected through commercially available avian reovirus antibody test kit (ELISA kit) and the virus induced a significant antibody titer indicating the affecting virus was absolutely ARV.Asian J. Med. Biol. Res. December 2015, 1(3): 612-621